First report of mixed infection of cassava brown streak virus and Ugandan cassava brown streak virus on cassava in north-eastern Democratic Republic of Congo - Casinga, C.M.; Monde, G.; Shirima, R.R.; Legg, James P. (Scientific Societies, 2019)
Cassava brown streak disease (CBSD), caused by two viruses (Cassava brown streak virus and Ugandan cassava brown streak virus) is one of the most important diseases affecting cassava in East and Central Africa. The viruses are spread through infected stem cuttings and by the whitefly Bemisia tabaci. Recognized from coastal East Africa since the 1930s, it is only in recent years that outbreaks have occurred in higher altitude areas of the African Great Lakes region (Legg et al. 2011). CBSD caused by UCBSV was officially reported for the first time from eastern Democratic Republic of Congo (DRC) in Nord-Kivu Province by Mulimbi et al. (2012). Eastern DRC is on the ‘front’ of the westwards-spreading pandemic of CBSD, and it is vital to understand the identity and epidemiology of viruses associated with this outbreak. If CBSV was to be reported from DRC, this increased diversity of CBSD-causing viruses would increase the threat posed by the disease and make management more difficult.